1993
DOI: 10.1093/infdis/168.2.476
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Hemolytic-Uremic Syndrome Relates to Erythrocyte Glycosphingolipid Patterns

Abstract: Hemolytic-uremic syndrome (HUS) is usually preceded by enteric infection by Shiga-like toxin-producing Escherichia coli (SLT-EC), but most children with SLT-EC diarrhea do not develop HUS. SLT toxicity depends on entry into the target cell via its host cell glycolipid receptor, globotriaosylceramide (Gb3). The relationship between differential susceptibility to HUS and erythrocyte Gb3 levels, as measured by high-pressure liquid chromatography, was studied. Erythrocytes of children with histories of HUS had low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…The upregulation by TNF-␣ of only one type of species, the NFA-Gb 3 s rather than the HFA-Gb 3 s, and the association of the NFA-Gb 3 species with Shiga toxin binding and toxicity are consistent with our hypothesis (25) that genetic heterogeneity in the expression of Gb 3 species may underlie differential susceptibility to HUS. This hypothesis may now be expanded to the involvement of the CNS in HUS, which may depend on heterogeneity in the expression of specific species of Gb 3 by the cerebral endothelial cells of individuals.…”
supporting
confidence: 85%
“…The upregulation by TNF-␣ of only one type of species, the NFA-Gb 3 s rather than the HFA-Gb 3 s, and the association of the NFA-Gb 3 species with Shiga toxin binding and toxicity are consistent with our hypothesis (25) that genetic heterogeneity in the expression of Gb 3 species may underlie differential susceptibility to HUS. This hypothesis may now be expanded to the involvement of the CNS in HUS, which may depend on heterogeneity in the expression of specific species of Gb 3 by the cerebral endothelial cells of individuals.…”
supporting
confidence: 85%
“…A similar hypothesis has been proposed for P blood types in human patients (32). However, a recent study refuted this possibility by showing that the P1 blood group was equally represented in healthy controls and E. coli O157:H7-infected children regardless of whether patients had uncomplicated illness or HUS (13), confirming the findings of previous studies that failed to associate P1 expression with diminished risk for the development of HUS after infection with E. coli O157:H7 (2,21,24,27).…”
Section: Discussionsupporting
confidence: 72%
“…Stx bind to human RBCs, monocytes, and neutrophils in vitro without causing morphological changes in these cells (4,26,34 (32). However, epidemiological data suggest that the P1 phenotype does not protect STEC-infected patients from HUS (2,13,21,24,27).…”
mentioning
confidence: 99%
“…It has been suggested that polymorphonuclear leukocytes, 17 monocytes, 44 or erthrocytes 60,61 may transport Stx in the circulation from the intestine to the kidney. The results of this investigation suggest that on contact with the intestinal circulation, Stx may bind to platelets and to other blood cells.…”
Section: Discussionmentioning
confidence: 99%